Analisa Tahanan Isolasi Pada Transformator Daya 20 MVA Di Gardu Induk ULTG Ende - Titiek Suheta; Muhamad Zainudin Abdul Medjid; Khoirul Anwar (Jurnal JEETech, 2024)
Power transformers are the main equipment in the electrical power system that is directly related to the distribution of electricity. One of the most important parts of a power transformer is its insulation system. Over time and operation, the condition of the insulation can deteriorate, which can cause operational failures and damage to the transformer. The purpose of the study was to determine the condition of the quality of insulation resistance in power transformers. The method was a literature study used to deepen the material related to the research title and data collection at the ULTG Ende Substation. The data taken were the results of polarization index, tangent delta and breakdown voltage tests. Based on the analysis results, the polarization index value in 2020 on the primary-ground side was 1.21 and the primary-secondary side was 1.23, but in 2022 it increased to 1.27 and 1.28. The tangent delta calculation results in 2020 on the secondary side on the CLG insulation was 0.64% and in 2022 it was 0.58%, which showed a decrease in insulation (0.5% - 0.7%). For breakdown voltage in 2020 it was 42.2 kV and OLTC 32.4 kV and in 2022 it was 41.1 kV and OLTC was 31.4 kV.